Pranata laksitaning adicara: dinamika penggunaan bahasa oleh tokoh Pambiwara pernikahan adat Jawa di Desa Pendem, Kecamatan Junrejo, Kota Batu (1997-2021) - Nanda Setia; Kurniawan Eko Supeno (Historiography: Journal of Indonesian History and Education, 2022)
Language is the main component in the communication process which has an element of heterogeneity in every practice. The function of language itself is not just a means of communication but as a means of conveying the values of speech acts implicitly.  The use of language in the 'pambiwara' character in Javanese traditional weddings has its own variety and dynamics that influence the meaning behind its character. This study aims to determine the various dynamics of the language used by the Pambiwara figures of Javanese traditional marriages along with the development of the influence of globalization, precisely in Pendem Village, Junrejo District, Batu City. This writing uses a historical methodology with data obtained from direct interviews and video documentation of one of the Javanese traditional weddings in Pendem Village. The results of the study provide an overview of the various dynamics of the language used by the Pambiwara characters, the elements of beauty that characterize the Pambiwara language in its delivery, as well as the factors causing the variation in the language used. Bahasa merupakan komponen utama dalam proses komunikasi yang memiliki unsur heterogenitas dalam setiap praktiknya. Fungsi bahasa sendiri bukan hanya sekedar alat komunikasi melainkan sebagai sarana penyampaian nilai-nilai dan tindak tutur.  Penggunaan bahasa pada tokoh pewara ‘pambiwara’ dalam pernikahan adat Jawa memiliki ragam dan dinamika tersendiri yang mempengaruhi makna dibalik pembawaannya itu. Penelitian ini bertujuan untuk mengetahui berbagai dinamika bahasa yang digunakan oleh tokoh Pambiwara pernikahan adat Jawa seiring dengan berkembangnya pengaruh globalisasi, tepatnya di Desa Pendem, Kecamatan Junrejo, Kota Batu. Penulisan ini menggunakan metodologi sejarah dengan data diperoleh dari wawancara langsung dan video dokumentasi salah satu pernikahan adat Jawa di Desa Pendem. Hasil penelitian memberikan gambaran mengenai berbagai macam dinamika bahasa yang digunakan oleh tokoh pambiwara, unsur-unsur keindahan yang mewarnai bahasa Pambiwara dalam penyampaianya, serta faktor penyebab ragamnya bahasa yang digunakan.